Spatial Modeling of Land Suitability of Various Industries in East Serang Region Based on the Spatial Plan of Serang Regency of 2011-2031 - Yetti Anita Sari; Amrih Halil (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
Industrial land suitability is a land assessment to be developed as an industrial area. Eastern Serang Regency is projected as a various industrial area following the Regional Regulation Number 5 of 2020. In examining potential lands to be developed as a various industrial area, a spatial modeling of land suitability is required. The parameters employed in this study were ten, comprising land use, slope, landslide, soil type, flood, erosion, drainage, water availability, waste disposal, and foundation stability. The study method was descriptive with a quantitative approach. The analysis technique was overlay and scoring techniques. The study aimed to 1) understand the location with an appropriate land area for a various industrial area and 2) calculate the land area potential to be developed as a various industrial area based on the spatial plan of Serang Regency. The study results are 1) the location with the biggest area based on the S2 land suitability class (appropriate) was Tunjungjeta District and 2) the overall area of land potential to be developed as a various industrial area based on the spatial plan of Serang Regency was 13661,36 Ha.